Feminismo De(s)colonial como Feminismo Subalterno Latino-Americano. - Ballestrin, Luciana Maria de Aragão (2021)
Submitted by Simone Maisonave (simonemaisonave@hotmail.com) on 2021-04-13T21:49:28Z No. of bitstreams: 2 license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5) Feminismo_De_s_colonial_como_Feminismo_Subalterno_Latino_Americano.pdf: 94949 bytes, checksum: c760524f699825f545964aea8cd783e5 (MD5)